Economic change in South-East Asia, c.1830-1980 - Brown, Ian (Oxford University Press, 1997)
This book provides an introduction to the economic history of South-East Asia from the early nineteenth century to the present. Topics include the strong commitment of rural South-East Asians to export production from the middle of the nineteenth century, the economic role of the Chinese, and the causes and nature of the region's modern industrialization.